2016
DOI: 10.1017/s174413311600027x
|View full text |Cite
|
Sign up to set email alerts
|

The double-edged sword of corporatisation in the hospital sector: evidence from Indonesia

Abstract: Hoping to improve their health system performance, many countries have corporatised their hospitals in the past twenty years. What this means for hospital performance remains as yet largely unknown. This study looks into the association of corporatisation and hospital performance in Indonesia. We apply panel data regression analysis to survey data on 54 public hospitals in East Java province. Our analysis suggests that corporatisation is associated with higher hospital income and expenditure, but fails to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, budgetary (A4) is the least appropriate organizational modality, with the utility function value of 0.5228. Such ranking can be decisive for healthcare managers and policy makers during the transitional period of healthcare industry into a market-based entity through restructuring the organizational aspects of the service providers, since according to some studies, restructuring healthcare organizations and the transition of service delivery to market-type mechanisms needs a long-term planning with a precious analysis of organizational environment and warn healthcare managers and politicians of severe costs and backlash if such transition happens without a situational analysis and in a go; A fact that shows such restructuring programs cannot be applied to all organizations with different circumstances with a single framework and more importantly needs to be done in a form of step by step process of restructuring towards a fully private structure providing healthcare services [ 42 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, budgetary (A4) is the least appropriate organizational modality, with the utility function value of 0.5228. Such ranking can be decisive for healthcare managers and policy makers during the transitional period of healthcare industry into a market-based entity through restructuring the organizational aspects of the service providers, since according to some studies, restructuring healthcare organizations and the transition of service delivery to market-type mechanisms needs a long-term planning with a precious analysis of organizational environment and warn healthcare managers and politicians of severe costs and backlash if such transition happens without a situational analysis and in a go; A fact that shows such restructuring programs cannot be applied to all organizations with different circumstances with a single framework and more importantly needs to be done in a form of step by step process of restructuring towards a fully private structure providing healthcare services [ 42 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Maharani and Tampubolon (2017), by extending research conducted by Suwandono et al (2001), reported that autonomization and devolution efforts on public hospitals do not necessarily improve either their financial performance or their utilization as measured by bed occupancy rates and number of procedures. Following trends in many countries that have improved their public hospitals' performance through corporatization type of decentralization (Preker& Harding, 2003, p. 10 (Maharani & Tampubolon, 2017). Maharani and Tampubolon (2017) reported that corporatization, indeed, has improved revenue and expenditure of the Indonesian public hospitals but not efficiency and equity.…”
Section: Benefit Utilizationmentioning
confidence: 95%
“…by giving public hospitals at provincial and district levels more authority to manage personnel, finance and procurement (Heywood & Harahap, 2009;Lieberman & Alkatiri, 2003;Maharani & Tampubolon, 2014). However, Maharani and Tampubolon (2017), by extending research conducted by Suwandono et al (2001), reported that autonomization and devolution efforts on public hospitals do not necessarily improve either their financial performance or their utilization as measured by bed occupancy rates and number of procedures. Following trends in many countries that have improved their public hospitals' performance through corporatization type of decentralization (Preker& Harding, 2003, p. 10 (Maharani & Tampubolon, 2017).…”
Section: Benefit Utilizationmentioning
confidence: 99%
See 2 more Smart Citations